Hey, dollface - Hautzig, Deborah (New York Knopf, 1989)
Two 15-year-old classmates are loving and devoted "best friends," but the time comes when they must ask themselves a hard question about their relationship.
"Borzoi sprinters."
UCWS-2013-G-956 donated by Gender Committee University Student Council 2011-2013 U.P. Diliman
Keywords: Coming out (Sexual orientation) -- Juvenile fiction; Friendship -- Juvenile fiction; Lesbian teenagers -- Juvenile fiction